Retrocaval Ureter: Report of Two Cases. (3rd November 2019) - Atawurah, Henry; Maison, Patrick Opoku Manu; Owusu-Ansah, Mohammed; Asante-Asamani, Alvin
Abstract : Retrocaval ureter (RCU) is a rare congenital anomaly in which the ureter passes posterior to the inferior vena cava (IVC). A little over 200 cases have been reported worldwide since Hochstetter's first report in 1893. We present two cases of retrocaval ureter which were successfully managed at the Cape Coast Teaching Hospital in Ghana. Case 1. A 55-year-old woman presented with a history of dull right flank pain of 2 years duration. Physical examination and basic laboratory investigations performed on her were normal. Abdominal ultrasound showed right hydronephrosis and a retrograde right ureteropyelogram (RPG) showed right hydroureteronephrosis with an "S" shaped proximal ureter. A diagnosis of retrocaval ureter was made and confirmed at surgery. Case 2. A 25-year-old man presented with dull intermittent right flank pain of 1 year duration. Clinical examination and laboratory investigation were normal. Abdominal ultrasound showed right hydronephrosis and a CT urogram made a diagnosis of retrocaval ureter which was confirmed at surgery. Conclusion. Retrocaval ureter is a rare congenital anomaly that is now increasingly being reported. Surgical treatment of symptomatic cases successfully relieves symptoms.